PROGRAM SENTONO MENABUNG - Lail, Jamalul (AJIE (Asian Journal of Innovation and Entrepreneurship), 2015)
Attitude fond of saving needs to be instilled in children from an early age to avoid the behavior of shoppers. The author tried to instill awareness fond of saving on children of Sentono village with variety of interesting wayss named Sentono Savings Program. Children are expected to remain consistent saving although the program finished running.